2015
DOI: 10.1039/c5cc01266j
|View full text |Cite
|
Sign up to set email alerts
|

Artificial receptors for nitrate: a comprehensive overview

Abstract: This feature article highlights recent developments in the field of synthetic receptors designed to recognize nitrate with a particular emphasis on: (i) synthetic receptors for nitrate in competitive media, (ii) assembly processes driven by nitrate recognition and (iii) synthetic transporters and extractants for nitrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Theo bserved selectivity for sulfate and nitrate stands in direct contrast with the anion selectivity in competitive crystallization of plain guanidinium salts,w hich favored the least hydrophilic perchlorate anion, in agreement with the Hofmeister bias. [17] Thep resence of sulfate in seawater presents challenges for oil field injection operations because of scale formation. Furthermore,a st he GBAH ligand was generated by hydrazone condensation, ar eversible bondforming reaction commonly employed in dynamic combinatorial chemistry (DCC), [16] it may be expected that even less soluble and more selective sulfate crystallization systems could be identified by DCC.M eanwhile,t he current system may already find practical applications related to sulfate or/ and nitrate separation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theo bserved selectivity for sulfate and nitrate stands in direct contrast with the anion selectivity in competitive crystallization of plain guanidinium salts,w hich favored the least hydrophilic perchlorate anion, in agreement with the Hofmeister bias. [17] Thep resence of sulfate in seawater presents challenges for oil field injection operations because of scale formation. Furthermore,a st he GBAH ligand was generated by hydrazone condensation, ar eversible bondforming reaction commonly employed in dynamic combinatorial chemistry (DCC), [16] it may be expected that even less soluble and more selective sulfate crystallization systems could be identified by DCC.M eanwhile,t he current system may already find practical applications related to sulfate or/ and nitrate separation.…”
Section: Methodsmentioning
confidence: 99%
“…Fore xample,b oth sulfate and nitrate can pose environmental problems as they are the main constituents of acid rain and can contaminate the groundwater. [17] Thep resence of sulfate in seawater presents challenges for oil field injection operations because of scale formation. [18] Sulfate is also ap roblematic constituent of legacy nuclear wastes, [3] which could be targeted for sulfate separation alongside the more abundant nitrate.W eenvision that this crystallization approach could be applied to either the individual separation of sulfate or nitrate or amixture of the two anions,d epending on the practical need and the solution composition.…”
Section: Methodsmentioning
confidence: 99%
“…4 Therefore, the development of artificial receptors with an affinity and specificity approaching biological receptors is a fundamental challenge in molecular recognition. [5][6][7] New strategies tested in this challenge could have an important long-term significance. Molecular imprinting is a powerful technology with the property of special recognition of the target molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[6] To date only arelatively small number of nitrateselective tripodal acyclic,m acrocyclic and cage-like host systems have been reported that utilise convergent hydrogen bonding (HB) and/or anion-p interactions to recognise the oxoanion in polar organic solvents. [7][8][9][10][11][12][13][14][15][16][17][18][19] Thec hallenge of developing synthetic receptors that can rival the anion recognition properties of biotic systems relies upon the arrangement of at hree-dimensional convergent array of numerous HB donor groups in an optimized geometry for recognition of the complementary guest. [20,21] To meet this challenge we have exploited anion-templation to construct interlocked host structures [22,23] whose unique threedimensional cavities encapsulate anionic guest species.…”
mentioning
confidence: 99%